The Effect of Rhinoceros Beetle Nanochitosan on Compressive Strength of Glass Ionomer Cement - Pratiwi, Deviyanti; Salim, Richentya Feiby; Komariah, Komariah (Indonesian Dental Association, 2021)
Introduction: : Glass Ionomer Cement (GIC) is a dental restorative material that is widely modified to improve mechanical properties, such as compressive strength. Biomaterial that can be used to modify GIC is nanochitosan, a material that has been studied to improve the mechanical properties of GIC. Nanochitosan from Xylotrupes gideon can increase enamel hardness on home bleaching application. Objective: To investigate the effect of nanochitosan from Xylotrupes gideon on compressive strength of GIC. Methods: The research type conducted was an experimental laboratory. Samples of 6 mm (height) × 4 mm (diameter) GIC divided into 10 groups (n=5) that was modified with 10% v/v nanochitosan solution, 5% v/v nanochitosan solution, 10% w/w nanochitosan powder, and with 5% w/w nanochitosan powder. Samples were stored in an incubator at 37°C for 1 hour and 24 hours before testing. Compressive strength was tested using Universal Testing Machine. Result: Nanochitosan modified GIC decreased in compressive strength. The result of Two-Way ANOVA statistical analysis showed that there was no significant difference (p >0.05) between all test groups, while there was a significant difference between the 1 hour and 24 hours test groups (p <0.05). Conclusion: Nanochitosan from Xylotrupes gideon has no significant effect on the compressive strength of GIC.